INTERNATIONAL ACCOUNTING TERMINOLOGY [The Accounting Acronyms major World] - Valdivia Ramos, Román Arturo (2013)
This investigation is the beginning of a long hard work, in which will make us know a more detailed classification of international accounting terminology. The second objet in a future the faculty of accounting sciences of the UNMSM (the first one, the best one and with the mayor prestige between other similar in the country), between his three academic of professionals, teach the class named international accounting terminology, in which the students learns history, characteristics, performance and other different groups or institutions internationals of accounting on the world. Little we know of them and if there is any studding of counting that does not know what happen in the world of counting, that is to say outside of the country, for sure will be in notable disadvantage with the others from a different counties.